Evaluasi Implementasi Kurikulum Merdeka pada Sekolah Menengah Kejuruan Pusat Keunggulan di Kota Sorong - Reny Azraeny. M; Hasanah Nur; Anas Arfandi (SEMINAR NASIONAL DIES NATALIS 62, 2023)
This research is an evaluation study using the CIPP model which concern to evaluate the implementation of the Independent Curriculum at the Center for Excellence Vocational High School with a focus on achieving context, input, process, and product. The informants in this study consisted of school supervisors, principals, vice principals, and tenth and eleventh grade subject teachers who were taken using a purposive sampling technique. Data collection techniques through observation, interviews, and documentation. The data analysis technique used is descriptive analysis. The results of the study show that: (1) Evaluation of the curriculum implementation context in the form of suitability of school criteria, content standards, vision, mission and school goals is sufficient to support the implementation of the Independent Curriculum; (2) Evaluation of inputs in the form of readiness, understanding, preparation, and infrastructure is quite ready even though there are components of facilities and infrastructure that need to be further optimized; (3) Evaluation of the process in the form of implementing the Independent Curriculum has not been maximized because there are still teachers who still use old techniques in learning, have not implemented assessments, have not implemented the Pancasila Student Profile Strengthening Project, and the infrastructure has not been optimal; (4) Product evaluation of the implementation of the Independent Curriculum is good enough in terms of the positive impact given in the form of increased learning outcomes and student activity in learning as well as motivation and achievement in participating in competitions. The conclusion from the research results is that the evaluation of the implementation of the Independent Curriculum at the Center for Excellence Vocational School is quite good because it can be seen from the increased student learning outcomes. Based on the conclusions of the research results, several recommendations can be submitted to the Education Office regarding the need for mentoring activities to improve teacher performance both in terms of improving the quality of learning, learning assessment, implementing the Project for Strengthening profile of Pancasila Student, and assisting in determining policy steps in making improvements to the implementation of the Independent Curriculum.